2008
DOI: 10.1111/j.1752-1688.2008.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Water‐Yield Reduction After Afforestation and Related Processes in the Semiarid Liupan Mountains, Northwest China1

Abstract: The increase of coverage of forest ⁄ vegetation is imperative to improve the environment in dry-land areas of China, especially for protecting soil against serious erosion and sandstorms. However, inherent severe water shortages, drought stresses, and increasing water use competition greatly restrict the reforestation. Notably, the water-yield reduction after afforestation generates intense debate about the correct approach to afforestation and forest management in dry-land areas. However, most studies on wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 28 publications
1
49
1
Order By: Relevance
“…Furthermore, the unit changes in both of them are over 5. This pattern was found in 16,7,18,23,26,30, 33 and 10 sub-watersheds. Most of them are located in the southeast of Dali County, especially in the staggered zone of Wood Land, Grassland and Dry Land.…”
Section: Driven Factors Of Relative Capacity Change On Water Yieldmentioning
confidence: 69%
See 2 more Smart Citations
“…Furthermore, the unit changes in both of them are over 5. This pattern was found in 16,7,18,23,26,30, 33 and 10 sub-watersheds. Most of them are located in the southeast of Dali County, especially in the staggered zone of Wood Land, Grassland and Dry Land.…”
Section: Driven Factors Of Relative Capacity Change On Water Yieldmentioning
confidence: 69%
“…There is a marked difference for the net water yield among the vegetation types [23,24]. For the different ET values, the grassland produces a higher water yield, the shrub forest provides a lower one, and the forest obtains the least one [23]. Consequently, units which have applied the grassland restoration policy will obtain a higher relative capacity.…”
Section: Driven Factors Of Relative Capacity Change On Water Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…3) (2014) modeled the net primary productivity of terrestrial ecosystem in China, and the value of average annual NPP in the Yanhe Basin was 300-500 g C/m 2 in 2005 (Yuan et al, 2014). Other studies also indicated that NPP showed a continuously increasing trend in the Yanhe Basin or most area of Loess Plateau during 2000-2008(Su et al, 2012Su and Fu, 2013;Xie et al, 2014). The total annual NPP for forest, shrub and grass were 1.7 × 10 9 g C, 3.12 × 10 9 g C and 2.167 × 10 10 g C in 2008, which increased by 91.2%, 139.8% and 242.7% is worth noting that the Yanhe Basin is located in FOR-GRASS zone .…”
Section: Changes In Annual Npp Over Yanhe Basinmentioning
confidence: 97%
“…4 1991-2000-2008(Ren et al, 2012. Based on data collected from hydrological station, Zhao et al (2014) reported a continuous decline for the runoff depth in the Yanhe Basin since 1997, and the average value of annual runoff depth was 24.76 mm between 1997 and 2010 .…”
Section: Changes In Annual Water Yield (Wy) Over Yanhe Basinmentioning
confidence: 99%